Heavy rainfall in Pakistan during 27-29 July 2010: Role of atmospheric energy conversion characteristics (MAUSAM, 2014)
Extreme weather events over Asia particularly in Pakistan are becoming more frequent in the present decade or so. This is contributing to the ever increasing human suffering of the region. In this study the whole energy parameter E from atmospheric energetic theory is derived. The characteristics of atmospheric energy conversion during the heavy rainfall in Pakistan for the period 27-29 July, 2010 are also discussed. The results show that due to the impact of the atmospheric circulation and terrain conditions, the kinetic energy is converted into potential energy, in the form of standing wave, during heavy rainfall development period. The conversion between kinetic and potential energy is significant in heavy rainfall spell. High energy value corresponds to the heavy rainfall region.